Prosthetic rehabilitation in the Posterior Mandible with Tissue Level Implant: A Case Report - Lamichhane, K; Pradhan, S; Gorkhali, R; Shrestha, B (Journal of Nepalese Prosthodontic Society, 2023)
Implant is becoming the most appropriate option nowadays for replacement of single or multiple missing teeth which offers the predictable long-term results. Continuous innovations in implant design and approaches for placement have been proposed to achieve good osseointegration, esthetics and predictable soft tissue contour. Soft tissue level (STL) implants are placed trans-mucosally with platform away from alveolar bone crest so the microbial deposits in the micro-gap at implant abutment connection has less effect on alveolar bone. This type of implant has a rough surface placed subcrestally to facilitate osseointegration and a polished coronal part to facilitate soft tissue adaptation. This case report highlights about soft tissue level implant, its advantages and clinical success on replacing single missing posterior tooth.